Unusual enhancement patterns from inadvertent arterial contrast injection during CT angiography. (August 2020) - Wong, Monica; Brennan, Daniel; Gaillard, Frank
Highlights: Arterial contrast injection can lead to non-diagnostic intracranial studies. This leads to further investigation, increasing patient dose and delaying management. We describe two cases of arterial contrast administration. Various enhancement patterns in normal and variant anatomy are also described. We aim to improve recognition of arterial contrast injection in a timely fashion. Abstract: Investigation of cerebrovascular incidents typically involve non-contrast intracranial computed tomography (CT) and CT angiography (CTA) of the arch of aorta to vertex with or without CT perfusion. Though rare, inadvertent direct arterial contrast injection is a potentially serious complication which can alter contrast distribution and timing resulting in non-diagnostic intracranial studies. If unnoticed, they can be misinterpreted as pathology leading to further unnecessary investigations, increasing patient radiation dose and delaying appropriate management. To date, there have been two documented case reports describing arterial contrast injection in cerebral CTA or CT perfusion. We describe two further cases of arterial contrast administration. Furthermore, by describing various contrast enhancement patterns in normal and variant anatomy – such as bovine aortic arch, vertebral artery dominance, posterior inferior cerebellar artery (PICA) continuation of vertebral artery and fetal posterior communicating artery (PCOM) – we hope to improve clinician recognition of inadvertent arterial contrast injection in a timely fashion.